Case Report: DRESS Syndrome Induced by Two Antituberculosis Drugs in an 8-Year-Old Girl - Urbonas, Vaidotas; Varnas, Dominykas; Mociskiene, Kristina; Kvedariene, Violeta; Rudzeviciene, Odilija (Frontiers in Pediatrics, 2022)
DRESS syndrome is defined as drug induced hypersensitivity syndrome with rash, eosinophilia, and systemic symptoms. This syndrome is mostly associated with anticonvulsants, antibacterial and anti-inflammatory drugs. DRESS syndrome is a rare disease and more frequently seen in adults. We present the first case report of DRESS syndrome in eight years old girl, after 3 months treatment with antituberculosis drugs (isoniazid and rifampicin). After discontinuation of drugs and short course of prednisolone girl recovered. After five years of follow up she is healthy and has no complaints but patch tests to isoniazid and rifampicin are positive. The reported case emphasizes the importance of thorough medical history and including drug reactions in differential diagnosis.